INTERACTION OF OBJECT, SUBJECT AND SYNERGETIC CATEGORIES IN SCIENTIFIC WORK - Karimova Muyassarkhan Abduqayumovna (Journals Park Publishing, 2022)
This article is about one of the most fundamental categories of philosophy, the object and the subject, and focuses on its place and role in scientific research. The objective of the research activity is the object in the broadest sense of reality. The researcher acts as a subject, whether it is an individual or a specific community (creative team). Synergetics has gained the status of a philosophical category as a branch of science and is important in the study of significant changes in the universe.
Keywords: object; subject; synergetics